Analisis Berita Politik Di Koran Bintang Borneo Pada Tahun 1929-1930 - Rahayu, Dian Budi (Langgong: Jurnal Ilmu Sosial dan Humaniora, 2023)
Social life in the political field in the Bintang Borneo Newspaper was based on the government in 1929-1930. This research aims to find out: (1) Find out about political problems in 1929. (2) Find out about political problems in 1930. This research uses the methods used are critical discourse, content analysis and framing analysis. This method is often used in political news analysis. The results of this research show that the political news conveyed in the Bintang Borneo newspaper does not only discuss political conditions in Kalimantan, especially the banjars, but also discusses issues from outside the region such as Java and even discusses problems abroad.